The Effect of Canva-Based Learning Media on Students’ Learning Motivation in Islamic Religious Education at Junior High School: Pengaruh Media pembelajaran berbasis Canva terhadap Motivasi Belajar Pendidikan Agama Islam Siswa Sekolah Menengah Pertama - Idhar Idhar; Ilyas Ilyas; Arif Rahman (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2025)
This study aims to analyze the effect of using Canva media on students’ learning motivation in Islamic Religious Education (IRE) at SMP Negeri 2 Dompu. The low level of students’ enthusiasm in IRE learning, which is still dominated by conventional methods, encourages the use of more innovative digital visual media. This study employed a quantitative ex post facto approach. The population consisted of 143 eighth-grade students, with 23 students selected as the sample through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression with SPSS version 25. The results showed that the use of Canva media had a significant effect on students’ learning motivation in IRE (t = 6.372; p < 0.05), with a coefficient of determination (R²) of 0.621. These findings indicate that Canva media is effective in increasing students’ interest, attention, and engagement in IRE learning. Therefore, the use of Canva is recommended as a creative and contextual learning medium in line with the Merdeka Curriculum.